2017
DOI: 10.1142/s0129055x17500210
|View full text |Cite
|
Sign up to set email alerts
|

Quantum theory in real Hilbert space: How the complex Hilbert space structure emerges from Poincaré symmetry

Abstract: As earlier conjectured by several authors and much later established by Solèr (relying on partial results by Piron, Maeda-Maeda and other authors), from the lattice-theory point of view, Quantum Mechanics may be formulated in real, complex or quaternionic Hilbert spaces only. Stückelberg provided some physical, but not mathematically rigorous, reasons for ruling out the real Hilbert space formulation, assuming that any formulation should encompass a statement of Heisenberg principle. Focusing on this issue fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(85 citation statements)
references
References 35 publications
1
84
0
Order By: Relevance
“…The main goal and result of this work is the proof that, also in the case of a quaternionic formulation with Poincaré symmetry, the theory can be re-formulated into a standard complex Hilbert space picture, where all self-adjoint operators represent observables, the standard version of Noether relation between continuous symmetries and conserved observables is restored and the notion of composite system can be implemented by the standard tensor product. The complex structure is, as in [23], uniquely imposed by Poicaré symmetry and is Poincaré invariant. We shall establish this result into a pair of distinct theorems.…”
Section: Main Results Of This Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The main goal and result of this work is the proof that, also in the case of a quaternionic formulation with Poincaré symmetry, the theory can be re-formulated into a standard complex Hilbert space picture, where all self-adjoint operators represent observables, the standard version of Noether relation between continuous symmetries and conserved observables is restored and the notion of composite system can be implemented by the standard tensor product. The complex structure is, as in [23], uniquely imposed by Poicaré symmetry and is Poincaré invariant. We shall establish this result into a pair of distinct theorems.…”
Section: Main Results Of This Workmentioning
confidence: 99%
“…On the other hand no quantum systems seem to exist that are naturally described in a real or quaternionic Hilbert space. In a previous paper [23], we showed that any quantum system which is elementary from the viewpoint of the Poincaré symmetry group and it is initially described in a real Hilbert space, it can also be described within the standard complex-Hilbert space framework. This complex description is unique and more precise than the real one as for instance, in the complex description, all self-adjoint operators represent observables defined by the symmetry group.…”
Section: November 06 2018mentioning
confidence: 99%
See 2 more Smart Citations
“…We shall not address here the problem of the apparent absence of physical systems described in real Hilbert spaces [St60,StGu61,MoOp17] and the possibility (or impossibility) of quaternionic formulations [FJSS62,Ad95,Gan17,MoOp17b]. Instead, we restrict attention to a celebrated result, provided by Gleason's theorem [Gl57], regarding the notion of quantum state.…”
Section: Gleason's Theorem and Troubles With The Quaternionic Formulamentioning
confidence: 99%